2018
DOI: 10.1007/s13205-018-1095-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from microwave-assisted acid or alkali-pretreated agricultural residues of cassava using separate hydrolysis and fermentation (SHF)

Abstract: The effect of microwave (MW)-assisted acid or alkali pretreatment (300 W, 7 min) followed by saccharification with a triple enzyme cocktail (Cellic, Optimash BG and Stargen) with or without detoxification mix on ethanol production from three cassava residues (stems, leaves and peels) by was investigated. Significantly higher fermentable sugar yields (54.58, 47.39 and 64.06 g/L from stems, leaves and peels, respectively) were obtained after 120 h saccharification from MW-assisted alkali-pretreated systems suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The reducing sugar consumption in F-SHF was worked out from the initial sugar concentration in the hydrolysate and the residual sugar concentration in the fermented broth. The other parameters related to ethanol fermentation were computed based on the previous reports ( Barcelos et al., 2011 ; Pereira et al., 2015 ; Yadav et al., 2011 ; Pooja et al., 2018 ) as given under: where Ef is the ethanol concentration (g/L) in fermented broth and W1 is the weight of dry biomass in one litre slurry where 0.82 is the specific gravity of ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The reducing sugar consumption in F-SHF was worked out from the initial sugar concentration in the hydrolysate and the residual sugar concentration in the fermented broth. The other parameters related to ethanol fermentation were computed based on the previous reports ( Barcelos et al., 2011 ; Pereira et al., 2015 ; Yadav et al., 2011 ; Pooja et al., 2018 ) as given under: where Ef is the ethanol concentration (g/L) in fermented broth and W1 is the weight of dry biomass in one litre slurry where 0.82 is the specific gravity of ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Potential residual biomass from post-harvest and agricultural production processes has been a target of revalorization through ethanol conversion due to its substantial generation rates and the fundamental structure of its saccharide components. Several studies have verified the data on bioethanol conversion from agricultural residues, for example from bagasse, rice husks, cassava peels and oil palm residues [20,[22][23][24]. Despite the properties of lignocellulosic biomass, lignocellulosic ethanol still faces certain constraints when it comes to developing it on an industrial scale [21,25,26].…”
Section: Introductionmentioning
confidence: 94%
“…They also confirmed the presence of fermentation inhibitors at high microwave power. Pooja et al [35] accomplished microwave-assisted acid/alkali pretreatment at 300 W for 7 min of agricultural residues of cassava. They suggested that microwave treatment is the most efficient pretreatment method.…”
Section: Microwave Pretreatment Of Wastementioning
confidence: 99%